The Role and Status of Food and Nutrition Literacy in Canadian School Curricula - Anderson, Heather; Falkenberg, Thomas (Alberta Journal of Educational Research, 2016)
The obesity epidemic in North America has given greater attention to food and nutrition literacy in Canadian schools. However, the review of relevant literature on food and nutrition literacy reveals quite a range of understandings of what such literacy means. This raises the question of what understanding of food and nutrition literacy is actually represented in Canadian curriculum documents, considering that it is the curriculum that primarily drives teaching and learning in schools? Using a document analysis approach, the study reported upon in this article enquires into this very question. While the study finds a range of conceptualizations represented across provinces, territories and subject areas, it identifies the preferred framing of food and nutrition literacy as being related to food consumption and health at the individual level. L’épidémie d’obésité en Amérique du nord a attiré une plus grande attention vers les connaissances en nutrition et en alimentation dans les écoles. Par contre, un examen de la littérature sur le sujet a révélé toute une gamme d’interprétations de ce qu’est une éducation en nutrition et en alimentation. La question suivante se pose alors : quelle représentation fait-on de la nutrition et l’alimentation dans les programmes d’études au Canada, le curriculum étant surtout ce qui véhicule ces connaissances? S’appuyant sur une approche d’analyse de documents, la présente étude s’est penchée sur cette question. Les résultats indiquent qu’il existe un éventail de conceptualisations selon les provinces, les territoires et la matière à l’étude, et que le cadre préféré pour aborder la consommation alimentaire et la santé repose sur l’individu.